Therapeutic Management of Subclinical Staphylococcus aureus Mastitis in Association with Iliofemoral Lymphadenopathy in a Cow - Steffl, Martin; Amselgruber, Werner M. (Journal of Advanced Veterinary Research, 2011)
A 6.5 year old Holstein-Friesian dairy cow was initially presented with anorexia and reduced milk yield. Subclinical mastitis was diagnosed by California Mastitis Test (CMT). Bacteriological examination of a milk sample of the affected hind quarter revealed the detection of S. aureus. Additionally, rectal examination revealed very large and hard iliofemoral lymph nodes. Iliofemoral lymphadenopathy was then confirmed by ultrasound examination. This unusual case suggests that S. aureus intramammary infection (IMI) may possess the ability to invade the host organism by lymphatic route without causing visible inflammatory reactions.